RELIABILITY ASSESSMENT OF WATER COOLING TOWER MODEL - Umurzaqova , G.; Xamroqulova , X. (Educational Research in Universal Sciences, 2023)
In modern heat exchange units, the greatest thermal resistance of heat transfer is observed in the front part of the wall. The rate of heat transfer is exceeded when the boundary layer is thinned or broken.